MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA SMP DENGAN METODE PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) PENDEKATAN SAINTIFIK - Zuli Nuraeni (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2017)
The type of this research is a Classroom Action Research (CAR) designed through Team Assisted Individualization (TAI) learning method with scientific approach to improving the students’ achievement in learning mathematics. The subject of this research are students in VIII B of SMP N 9 Yogyakarta. The data collection technique used in this research is observation and test. The data analysis technique used in this research is quantitative description for every cycle. The results finding shows before treatment, the students that get KKM value are 29.41% and the average of achievement value only 53.24. There is improvement in the last of first cycle, the average value of first cycle post test is 74.85, the students that get KKM value are 64.71%. And the last of second cycle, the average value of first cycle post test are 75.06, the students that get KKM value are 85.29%. So the improvement of the students’ achievement in learning mathematics throught the implementation of Team Assisted Individualization (TAI) learning method with scientific approach before treatment to the last of first cycle is 21.25 and the last of first cycle to the last of second cycle is 0.21.